Women's Theatre Writing in Victorian Britain - Newey, K. author. aut Link
IX, 269 p.
Keywords: Women's Theatre Writing in Victorian Britain is the first book to make a comprehensive study of women playwrights in the British theatre from 1820 to 1918. It looks at how women playwrights negotiated their personal and professional identities as writers, and examines the female tradition of playwriting which dramatises the central experience of women's lives around the themes of home, the nation, and the position of women in marriage and the family. The book also includes an extensive Appendix of authors and plays, which will be a useful reference tool for students and scholars in nineteenth-century studies and theatre historians.